2016
DOI: 10.1002/aic.15557
|View full text |Cite
|
Sign up to set email alerts
|

Droplet breakage and coalescence in liquid–liquid dispersions: Comparison of different kernels with EQMOM and QMOM

Abstract: Droplet coalescence and breakage in turbulent liquid–liquid dispersions is simulated by using computational fluid dynamics (CFD) and population balance modeling. The multifractal (MF) formalism that takes into account internal intermittency was here used for the first time to describe breakage and coalescence in a surfactant‐free dispersion. The log‐normal Extended Quadrature Method of Moments (EQMOM) was for the first time coupled with a CFD multiphase solver. To assess the accuracy of the model, predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 105 publications
(257 reference statements)
1
40
0
Order By: Relevance
“…QMOM and EQMOM have been recently compared in the study of liquid-liquid dispersion in a stirred tank [33,37]. Li et al [37] performed a comparison between QMOM and EQMOM in turbulent liquid-liquid dispersion, and they observed that these two methods provided similar predictions.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…QMOM and EQMOM have been recently compared in the study of liquid-liquid dispersion in a stirred tank [33,37]. Li et al [37] performed a comparison between QMOM and EQMOM in turbulent liquid-liquid dispersion, and they observed that these two methods provided similar predictions.…”
Section: Introductionmentioning
confidence: 89%
“…While this reconstruction is not unique for the set of transported moments, examining the reconstructed NDF can provide a better insight into the behavior of the dispersed phase. In order to plot NDF, weights and abscissae calculated by EQMOM and extracted from CFD-PBM solver are utilized to approximate Equation (37). Figure 4 indicates the shape of NDF in the liquid phase (water zone) at t = 60 s. It can be observed that the mean bubble diameter ranges from 1 mm to 6 mm, and thus, the monodispersity is not a suitable approximation.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their model predictions were validated against experimental data. Li et al compared EQMOM with QMOM in a turbulent liquid‐liquid mixing and they found these two approaches make similar predictions. They performed reconstruction of the droplet size distribution with the use of EQMOM.…”
Section: Introductionmentioning
confidence: 99%
“…To predict the evolution of DSD, the two‐fluid model coupled with a breakage and coalescence model have been adopted in the literature . The multifractal kernel model was successfully applied to predict the liquid‐liquid dispersions in stirred tanks by Li et al and Gao et al…”
Section: Introductionmentioning
confidence: 99%